Financial Literacy Movement: Student Financial Education Strategy through Partnerships between Universities and Financial Institutions - Henry Dunan Pardede; Hengki Mangiring Parulian Simarmata; Erwin Sirait; Natalia Pransiska Silaen; Andriano Simarmata (Lembaga Pengembangan Kinerja Dosen, 2025)
The low level of financial literacy among students is an important concern in the increasingly complex digital economy era. To address these issues, this Community Service activity promotes the theme